Web Based English Placement Test System (ELPTS) - Alhawamleh, Ahmad Mtair Khadair (2012)
The English language proficiency of international students admitted to study different academic programs in University of Utara Malaysia is of paramount importance. Students are expected to communicate satisfactorily (verbal and written) during the course of their studies. The presently conducted English placement test is paper-based, which is time consuming and effort spending. This study aims to develop a web-based English Language Placement Test; in order to reduce the time and efforts which are required in paper based tests. Therefore, Vaishnavi method is used to design and develop the prototype model. According to the requirements are collected through interview with both students and department staff. Moreover, the prototype model is proposed, and the system is developed. Furthermore, the user acceptance test is conducted.